Effect of sample temperature on laser-induced plasma of silicone rubber - An, Zhiguo; He, Yongqi; Chen, Qijuan; Du, Gang; Wang, Xilin (Frontiers in Physics, 2023)
Silicone rubber in power transmission and transformation equipment is subjected to considerable temperature changes under different application environment conditions and in different operational states. In tropical areas and the Turpan region of China, surface temperatures of silicone rubber insulators may reach or exceed 70 °C. During in situ testing of silicone rubber, the spectral signal may fluctuate or even be distorted when the temperature changes, and consequently, the accuracy of the analysis may be affected. Therefore, we performed a LIBS-based investigation into the dependence of the spectral signal of rubber silicone on the sample temperature. Using high-temperature vulcanized silicone rubber as the experimental material, we determined the trends in spectral line intensity for different elements, plasma temperature, and electron density with temperature when the sample temperature was increased from 25 °C to 310 °C. The results indicated that the intensities of the Al I 394.40 nm, Al I 396.15 nm, and Si I 390.55 nm lines in the LIBS spectra underwent a gradual decrease as the temperature was increased, whereas the intensity of the Al I 309.27 nm spectral line was essentially stable. However, the spectral line intensity, plasma temperature, and electron density all exhibited a spike at approximately 260 °C, which occurred because of the decomposition of aluminum hydroxide. The results of the present study should prove to be of significance in further increasing the accuracy of LIBS analysis as applied to silicone rubber surface monitoring in high-temperature environments.